Search

Robert Z.'s Resources

Answers

To use the quadratic formula, first put the equation in standard quadratic form: x2 - 6x +16 = 0 a = 1; b = -6; c =16   x = (6 ± √(36 - 64) / 2 x = 3 ± (√(-28)) / 2 x = 3 ± (√(4)√(-7)) / 2 x = 3 ± √(-7) The solutions are x = 3 + 7i and x = 3 - 7i,...

Answers

n + k = 16 nk =60   Substituting for n: 60/k+ k = 16   Multiplying both sides by k: 60 + k2 = 16k   Putting in standard quadratic form: k2 - 16k + 60 = 0   Technically, none of the answers provided is correct.  The...

Answers

Let F be the 1st number, S the 2nd. First condition: F = S - 5 Second condition: 3F = 6S + 6   Substituting for F:   3(S - 5)= 6S + 6 Expanding:            3S - 15 = 6S + 6 Solving:         ...

Answers
split room fees (answer)

I think there are 2 reasonable answers:   1) The people who staying in the room on a given night should split the cost evenly.  The room goes for $254 per night. When 5 people are staying, each should pay $254/5 = $50.80.  When 3 people are staying, each should pay $254/3 =...

Answers

Expand: 3t^2 + 6t = 1 Put in quadratic form: 3t^2 + 6t -1 = 0 a=3, b=6, c=-1 Apply the formula: t = [-b ± sqrt (b2 - 4ac)] / 2a   t = [-6 ± sqrt(36 +12)] / 6   Separate into 2 terms:          t = -1 ± sqrt...

Answers
collisions (answer)

Assuming the three components of the velocity are the standard x, y, and z, first apply the Law of Conservation of Linear Momentum to each component.  Momentum must be conserved along each of the 3 mutually perpendicular directions.   Part a. For the x, (.5)(2)kg-m/s + (1.5)(-1)kg-m/s...